Computers as components principles of embedded computer system design - Wolf Wayne (San Francisco Morgan Kaufmann, 2005)
This book aims to be a comprehensive introduction to modern embedded computing: high-performance microprocessors and high-level language programming serving complex applications. It unravels the complexity of these systems and the tools and methods neces
Keywords: Embedded computer systems; System design